Endovascular treatment of vein of Galen aneurysmal malformation using rapid ventricular pacing: A case report. Issue 1 (February 2017) - Ramgren, Birgitta; Rask, Olof; Gelberg, Jan; Liuba, Petru; Undrén, Per; Wassélius, Johan
The treatment of choice of vein of Galen aneurysmal malformation (VGAM) involves endovascular procedures that can be difficult to perform in high-flow fistulas. We describe the use of rapid ventricular pacing (RVP), a well-known cardiologic technique, to safely treat a high-flow fistula in an infant with VGAM.